Experimental Results of a Differential Angle-of-Arrival Based 2D Localization Method Using Signals of Opportunity. (25th March 2018) - Aziz, M. A.; Allen, C. T.
Abstract : This paper presents a study of differential AoA (Angle-of-Arrival) based 2D localization method utilizing FM radio signals (88 MHz–108 MHz) as Signals of Opportunity (SOP). Given prior knowledge of the transmitters' position and signal characteristics, the proposed technique utilizes triangulation to localize receiver's 2D position. Dual antenna interferometry provides the received signals' AoA required for triangulation. Reliance on precise knowledge of antenna system's orientation is removed by utilizing differential Angle of Arrivals (dAoAs). The 2D localization accuracy is improved by utilizing colocated transmitters, a concept proposed in this paper as supertowers. Analysis, simulation, and ground-based experiments have been presented; results showed that when the SNR (Signal-to-Noise Ratio) is higher than 45 dB, the proposed method localizes the receiver's 2D position with an error of less than 15 m.